2021
DOI: 10.1093/heapol/czab063
|View full text |Cite
|
Sign up to set email alerts
|

‘A seamless transition’: how to sustain a community health worker scheme within the health system of Gombe state, northeast Nigeria

Abstract: Health interventions introduced as part of donor-funded projects need careful planning if they are to survive when donor funding ends. In northeast Nigeria, the Gombe State Primary Health Care Development Agency and implementing partners recognized this when introducing a Village Health Worker (VHW) Scheme in 2016. VHWs are a new cadre of community health worker, providing maternal, newborn and child health-related messages, basic healthcare and making referrals to health facilities. This paper presents a qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…While the integration of maternal and newborn care delivery is important, specific newborn health programs need to be prioritized and funded with council administration [ 67 ] taking the lead with a health system-wide approach to guide and oversee the implementation, monitoring, evaluation, and learning. Actions to plan and ensure the sustainability of newborn health programs are important through building relationships with stakeholder groups, harnessing powerful champions’ support, and institutionalization of the program within-host routine health systems rather than in parallel implementation [ 68 ]. This will improve coverage, access, equity, and efficiency and ensure sustainability and system-wide strengthening for better health of an overall population.…”
Section: Discussionmentioning
confidence: 99%
“…While the integration of maternal and newborn care delivery is important, specific newborn health programs need to be prioritized and funded with council administration [ 67 ] taking the lead with a health system-wide approach to guide and oversee the implementation, monitoring, evaluation, and learning. Actions to plan and ensure the sustainability of newborn health programs are important through building relationships with stakeholder groups, harnessing powerful champions’ support, and institutionalization of the program within-host routine health systems rather than in parallel implementation [ 68 ]. This will improve coverage, access, equity, and efficiency and ensure sustainability and system-wide strengthening for better health of an overall population.…”
Section: Discussionmentioning
confidence: 99%
“…Components aimed to enhance uptake and provision of life-saving interventions at three interacting levels (individuals and families; community organisations; and the health system). At the individual and family level, interventions aimed to improve knowledge, attitudes and practices to increase enhanced home-based practices and increase demand for routine professional care; for example, a community-based village health worker home visit scheme was initiated to improve knowledge about and linkages between families and health services 33. At the community organisation level, interventions aimed to improve trust and accountability between the family and health system levels; for example, through supporting community-based mothers groups to interact with their local primary health services 34.…”
Section: Methodsmentioning
confidence: 99%
“…At the individual and family level, interventions aimed to improve knowledge, attitudes and practices to increase enhanced home-based practices and increase demand for routine professional care; for example, a community-based village health worker home visit scheme was initiated to improve knowledge about and linkages between families and health services. 33 At the community organisation level, interventions aimed to improve trust and accountability between the family and health system levels; for example, through supporting community-based mothers groups to interact with their local primary health services. 34 Interventions at the health system level aimed to improve the supply of safe, effective and high quality care; for example, working with government to strengthen the supply chain for essential drugs in PHCs.…”
Section: Setting and Intervention Implementationmentioning
confidence: 99%
“…This study identified that more than six donor-funded projects were sustained beyond the funding lifecycle from donor organizations. Despite the poor socioeconomic status in which most of the beneficiary communities existed, it could be inferred that communities mobilized internal support to sustain donor-funded health interventions [ 45 - 47 ]. This finding thus elucidates that the sustainability of health interventions does not rest solely on the oars of provisions from donors [ 48 ].…”
Section: Reviewmentioning
confidence: 99%
“…This study found that community acceptance of a health intervention through volunteerism is a core factor that drives the sustainability of any donor-funded project. This is because community engagement strategies are adopted at the onset of the project using a grassroots design that helps to create a sense of ownership and minimize dependency on the funding agencies at the community level [ 45 ]. As revealed in some studies included in this review, the intellectual, human, and material resources of the community are tapped into with the recognition that these resources are crucial to ensure the project of the success through the grassroots approach [ 36 - 38 ].…”
Section: Reviewmentioning
confidence: 99%